Hypothalamic and mesencephalic regions involved in the control of laryngeal activity and subglottic pressure in spontaneously breathing anaesthetized rats - González-García, Marta; López-González, Manuel Víctor; Carrillo-Franco, Laura; Carrillo-Franco, Cristina; Dawid-Milner, Marc Stefan (My University, 2019)
Changes of laryngeal caliber allow changes in airflow which are necessary for the vibration of the vocal folds and emission of voice. It is known that stimulation of the Periaqueductal Gray matter (PAG) and nucleus retroambiguus (nRA) produces vocalization, and lesions in PAG cause mutism in animals and humans. The nRA is the perfect target to turn passive into active expiration modifying the activity of laryngeal motoneurons located in the nucleus ambiguous (Paton and Nolan, 2000). We have shown that rostral and ventral pontine structures are involved in changes of laryngeal caliber (Lara et al., 2002). It has been also demonstrated a high expression of FOXP2 protein (transcription factor related to vocalization) at mesencephalic and pontine regions (PAG, Parabrachial complex and A5 Region) involved in cardiorespiratory control. The aim of this study was to characterize the relations between hypothalamic and mesencephalic regions involved in cardiorespiratory control and their possible role in modulating laryngeal activity. Experimental studies were carried out with non-inbred male rats (n=7), SPF, Sprague-Dawley (250-300 g) housed under standard conditions. Animals were anesthetized with sodium pentobarbitone (60 mg/kg i.p., initial dose, supplemented 2 mg/kg, i.v., as necessary). A double tracheal cannulation to develop the classical technique of the “glottis isolated in situ” and for the recording of respiratory airflow was carried out. DMH-PeF, dlPAG, and CnF stimulations evoked a significant decrease of laryngeal resistance (subglottal pressure) (p<0.01) accompanied with an inspiratory facilitatory response consisted of an increase in respiratory rate, together with a pressor and tachycardic response. The results of our study contribute with new data on the role of the hypothalamic-mesencephalic neuronal circuits in the control mechanisms of subglottic pressure and laryngeal activity.
Keywords: Subglottic Pressure; Laryngeal Motoneurons; DMH-PeF; dlPAG; Nucleus Ambiguus